CXCL12 and IL7R as Novel Therapeutic Targets for Liver Hepatocellular Carcinoma Are Correlated With Somatic Mutations and the Tumor Immunological Microenvironment - He, Ke; Liu, Shuai; Xia, Yong; Xu, Jianguo; Liu, Fei; Xiao, Jing; Li, Yong; Ding, Qianshan; Lu, Ligong; Xiang, Guoan; Zhan, Meixiao (Frontiers in Oncology, 2020)
The mechanism of liver hepatocellular carcinoma (LIHC) development in correlation with tumor microenvironments and somatic mutations is still being elucidated. This study aims to identify the potential molecular mechanisms and candidate biomarkers in response to tumor microenvironments and somatic mutations. Multiple bioinformatics analysis methods were applied to assess the tumor immunological microenvironment, differentially expressed genes, genetic function enrichment, immunocyte infiltration, regulatory network construction, and tumor mutational burden, and to identify DNA methylation sites. The immunological microenvironment features of ESTIMATE score (OS: p = 0.017, HR = 0.64; RFS: HR = 0.43, p < 0.001) have an important impact on the prognosis of LIHC patients. Cut-off by ESTIMATE score and prognostic information identified 666 DEGs (45 downregulated and 621 upregulated) that were linked with leukocyte migration and lymphocyte activation. In immunocyte infiltration analysis, NK cells (resting), M1 macrophages, CD8+ T cells, and regulatory T cells (Tregs), which are considered core immunoregulatory cells, exhibited significant differences between higher and lower ESTIMATE scores (overall survival and recurrence-free survival p-values < 0.01). Subsequently, further analysis of immunocyte-hub gene identification illustrated that the expression levels of CXCL12 and IL7R significantly correlated with core immunoregulatory cells and somatic mutations (CXCL12: p = 2.1E-06; IL7R: p = 0.001). This study provides new insight into our understanding of the mechanisms of immunocyte regulation and microenvironment involved in LIHC development as well as the effective biomarkers of CXCL12 and IL7R and core immunoregulatory cells, which may emerge as novel therapies for LIHC patients.